DESIGN OF A DECISION SUPPORT SYSTEM FOR CONTRACTOR SELECTION USING THE SAW (SIMPLE ADDITIVE WEIGHTING) METHOD. - Nurdiansyah Permana; Davit Hermawan; Raden Deden Ahmad Hidayat; Endra Abdul Hadi; Fikri Emsa Silmi (Politeknik Mardira Indonesia, 2025)
This decision support system is designed to address the problem of selecting the best contractor at PT Integrasi Kreasi Zee (Zee Studio), a crucial issue given the project's significance to the company. By implementing the Simple Additive Weighting (SAW) method, a weighted addition algorithm, this system provides a comprehensive analysis tool that enables decision-makers to solve complex problems and produce more qualified and appropriate contractor choices. The system development utilizes the Rational Unified Process (RUP) method to ensure a structured, iterative, and architecture-centered approach, thereby ensuring the resulting system functions optimally according to the company's operational needs and is easy to manage throughout its development life cycle.